2006
DOI: 10.1017/s0010417506000053
|View full text |Cite
|
Sign up to set email alerts
|

Goodness Is Elsewhere: The Rule of European Difference

Abstract: Reflecting on European colonialism in 1950—at a time when discussions about what we now know as the European Union emerged in western Europe—Aimé Césaire wrote, “… Europe is morally, spiritually indefensible.”2 This idea is fairly commonplace in much of the post-colonial world and it has some purchase within certain academic and intellectual circles elsewhere. And yet, in the process of denouncing the widely noted3 presence of racism in Hungary, thirty-six leading Hungarian intellectuals have, in a recent publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 3 publications
0
36
0
2
Order By: Relevance
“…Western Europeans have long viewed their region as more developed than the rest of Europe, and this perception was important in the way Europe was divided after World War II between "east" and "west" (Böröcz 2006, Melegh 2006, Todorova 1997, Wolff 1994. Perceptions of this developmental hierarchy have also influenced how Eastern European countries were evaluated for possible admission into the European Union (Böröcz 2000).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Western Europeans have long viewed their region as more developed than the rest of Europe, and this perception was important in the way Europe was divided after World War II between "east" and "west" (Böröcz 2006, Melegh 2006, Todorova 1997, Wolff 1994. Perceptions of this developmental hierarchy have also influenced how Eastern European countries were evaluated for possible admission into the European Union (Böröcz 2000).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“… 3 Although development has been typically understood as eternal accumulation of material wellbeing (Thornton 2005: 137–138; also see, e.g., Condorcet 1796; Ekirch 1951; Godwin 1926/1793; Hegel 1878/1837; Marx and Engels 1965/1848; Nibset 1980) and associated with positive ethics and morality (Böröcz 2006; Chabbott 1999; Latham 2000; Taylor 2004; Thornton et al 2010b; United Nations 2005–2012), we acknowledge that important alternatives do exist. For instance, it has been suggested that development is sometimes associated with excessive sex liberty, atheism, violence, etc.…”
mentioning
confidence: 99%
“…As cultural diplomacy and the 'soft power' of culture and arts programs continue to be heralded, the EU is preparing to transpose its 'civilizing impact' onto other geopolitical areas. Claiming that Europe, in contrast to the U.S., values culture, proponents of such a European foreign cultural policy attempt to establish the EU as operating from a moral high ground (Böröcz 2006).…”
Section: Discussionmentioning
confidence: 99%